Effects of Different Levels of Garlic Straw Powder on Growth Performance, Meat Quality, Antioxidant and Intestinal Mucosal Morphology of Yellow-Feathered Broilers - Liao, Shuang; Liao, Liping; Huang, Peng; Wang, Yanzhou; Zhu, Siyuan; Wang, Xin; Lv, Tuo; Li, Yinghui; Fan, Zhiyong; Liu, Touming; Lin, Qian (Frontiers in Physiology, 2022)
The full utilization of garlic straw can partially alleviate shortage of feedstuff and waste of resources. The purpose of this study was to investigate the effects of garlic straw as an unconventional feed on yellow-feathered broilers. 360 28-day-old yellow-feathered broilers were randomly divided into 4 groups with 6 replicates (cage) per group, 15 per cage. The 4 groups were as follows: control group (basal diet) and experimental group I (basal diet supplemented with 3% garlic straw powder), II (basal diet supplemented with 6% garlic straw powder) and III (basal diet supplemented with 9% garlic straw powder). There was no significant difference in the initial body weight of the broilers among groups (p > 0.05). The test period was 28 days in total. The experiment results showed that there were no significant difference in the average final weight, ADG, ADFI and F/G among groups (p > 0.05). On the one hand, for the breast muscle, the drip loss of experimental group I, II and III were reduced by 17.24% (p <0.05), 20.11% (p <0.05) and 20.50% (p <0.05), respectively, compared with the control group; the redness a* of the experimental groups had a trend of improvement (0.05 <p < 0.1). On the other hand, compared with the control group, the redness a* of the experimental group II increased significantly by 23.18% for the leg muscles (p < 0.05). Furthermore, compared with the control group, GSH-Px of the experimental group III significantly increased by 21.38% (p < 0.05), and SOD of the experimental group I significantly increased by 21.85% (p < 0.05). Finally, there were no significant differences in the intestinal villus height, crypt depth, V/C and intestinal wall thickness among four groups (p >0.05). In conclusion, dietary supplementation of different levels of garlic straw powder can improve meat quality and antioxidant capacity of yellow-feathered broilers without affecting growth performance and intestinal mucosal morphology.